Anti-inflammatory effects of the willow bark extract STW 33-I (Proaktiv) in LPS-activated human monocytes and differentiated macrophages - Bonaterra, Gabriel; Heinrich, E. U.; Kelber, O.; Weiser, D.; Metz, Jürgen; Kinscherf, Ralf (Phytomedicine, 2010)
Introduction - Willow bark extract is frequently used in the treatment of painful rheumatological diseases, such as arthritis and back pain. Its effect has been attributed to its main component salicin, but pharmacological studies have shown that the clinical efficacy of the willow bark extract cannot be explained by its salicin content alone. Therefore different modes of action have been suggested for the anti-inflammatory effect of willow bark extract. Here, we report in vitro data revelling the effect and mode of action of the aqueous willow bark extract STW 33-I as well as a water-soluble fraction (fraction E [Fr E]) in comparison with well-known non-steroidal anti-inflammatory drugs (NSAIDs) like aspirin (ASA) and diclofenac (Diclo) on pro-inflammatorily activated human monocytes and differentiated macrophages. - Results - STW 33-I and the water-soluble Fr E showed concentration-dependent and significant anti-inflammatory effects in lipopolysaccharide-activated monocytes. Both inhibited the intracellular protein expression of tumour necrosis factor-alpha (TNFα) as well as the mRNA expression of TNFα and cyclooxygenase 2 (COX-2), and the release of nitric oxide (NO). In addition, apoptosis of pro-inflammatorily activated monocytes was induced. Furthermore, treatment of activated macrophages with STW 33-I inhibited the nuclear translocation of the p65 subunit of the nuclear transcription factor-kappa B (NF-κB p65). - Conclusions - The present in vitro investigations suggest a significant anti-inflammatory activity of willow bark water extract STW 33-1 and of its water-soluble fraction by inhibiting pro-inflammatory cytokines (TNFα), COX-2 and nuclear translocation of the transcription factor NF-κB in pro-inflammatorily activated monocytes. Our results provide further evidence for the therapeutic use of STW 33-I in inflammation-related disorders.